2021
DOI: 10.1111/ajt.16281
|View full text |Cite
|
Sign up to set email alerts
|

Understanding family dynamics in adult-to-adult living donor liver transplantation decision-making in Taiwan: Motivation, communication, and ambivalence

Abstract: This study investigated how multiple family members co‐construct the ethical significance of living donor liver transplantation (LDLT) and how the family structure and dynamics of donor–recipient–caregiver relationships shape the communication and decision‐making process within the sociocultural context of Taiwan. We conducted in‐depth interviews with 36 participants from 13 families at the Chang Gung Memorial Hospital from February to December 2019. Interviews were audio recorded, transcribed, and translated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Previous studies often simply described the decision-making model as family centered ( 35 ). Ya-Ping Lin had constructed 3 patterns of communication and decision-making processes in living donor liver transplantation among Tawanese ( 26 ). However, we established three family communication patterns that apply to the public in China mainland based on varying family structures, relationships, personal attitude and traditional beliefs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies often simply described the decision-making model as family centered ( 35 ). Ya-Ping Lin had constructed 3 patterns of communication and decision-making processes in living donor liver transplantation among Tawanese ( 26 ). However, we established three family communication patterns that apply to the public in China mainland based on varying family structures, relationships, personal attitude and traditional beliefs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research focused on family’s attitude toward donation ( 22 ), family bereavement ( 23 ), influencing factors ( 24 ), ethical exploration ( 25 ) and motivation to donate ( 26 ). Many of these studies were conducted in the United States, Australia, Canada and the United Kingdom.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22] Apart from this, familial common good and mutual obligation are also strongly emphasized in many Asian countries; therefore, the number of living donor kidney transplants is signi cantly higher than that in other countries when considering the total number of transplantations, even without any special encouragement. [22] In this study, the willingness to donate a kidney was about half, and the targets of donations mainly were family members. There seems to be no great reluctance to donate a kidney to family members, probably because this may have originated from the aforementioned Asian culture that values family relations.…”
Section: Discussionmentioning
confidence: 99%
“…[19,20] Additionally, the reasons why deceased donor transplantation has not been performed in Korea are as follows: 1) the leading cause of brain death, such as death from head trauma caused by tra c or cerebrovascular accident, is high; and 2) the rapid transition to an aging society has led to an increase in the number of brain deaths in elderly patients with various underlying diseases, so organs that can be donated are often limited. [19][20][21][22] Apart from this, familial common good and mutual obligation are also strongly emphasized in many Asian countries; therefore, the number of living donor kidney transplants is signi cantly higher than that in other countries when considering the total number of transplantations, even without any special encouragement. [22] In this study, the willingness to donate a kidney was about half, and the targets of donations mainly were family members.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22] Apart from this, familial common good and mutual obligation are also strongly emphasized in many Asian countries; therefore, the number of living donor kidney transplants are signi cantly higher than that in other countries when considering the total number of transplantations, even without any special encouragement. [22] In this study, the willingness to donate a kidney was found to be about half, and the targets of donations were mostly family members. There seems to be no great reluctance to donate a kidney to family members, probably because this may have originated from the aforementioned Asian culture that values family relations.…”
Section: Discussionmentioning
confidence: 99%